2019
DOI: 10.1111/risa.13312
|View full text |Cite
|
Sign up to set email alerts
|

Potential Airborne Asbestos Exposure and Risk Associated with the Historical Use of Cosmetic Talcum Powder Products

Abstract: Over time, concerns have been raised regarding the potential for human exposure and risk from asbestos in cosmetic-talc-containing consumer products. In 1985, the U.S. Food and Drug Administration (FDA) conducted a risk assessment evaluating the potential inhalation asbestos exposure associated with the cosmetic talc consumer use scenario of powdering an infant during diapering, and found that risks were below levels associated with background asbestos exposures and risk. However, given the scope and age of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 52 publications
(101 reference statements)
0
8
0
1
Order By: Relevance
“…Burns ve arkadaşlarının yaptığı bu çalışmada iki yıl boyunca pudralanan yenidoğanlarda akciğer kanseri ve mezotelyoma riskini değerlendirmek amacıyla 0.020 IUR (Inhalation Unit Risk) teorik risk faktörü hesaplanmıştır. Ancak, yaşam boyu kümülatif maruziyet değerleri hesaplandığında, Amerika Birleşik Devletleri'ndeki asbest risk değerlendirmesi düzenleyici modeli ile elde edilen bu teorik veri EPA'nın (Environmental Protection Agency) kanser riskine ilişkin hedef risk seviyesinin altında bulunmuştur [71].…”
Section: Asbest Ve Talk Pudrasıunclassified
“…Burns ve arkadaşlarının yaptığı bu çalışmada iki yıl boyunca pudralanan yenidoğanlarda akciğer kanseri ve mezotelyoma riskini değerlendirmek amacıyla 0.020 IUR (Inhalation Unit Risk) teorik risk faktörü hesaplanmıştır. Ancak, yaşam boyu kümülatif maruziyet değerleri hesaplandığında, Amerika Birleşik Devletleri'ndeki asbest risk değerlendirmesi düzenleyici modeli ile elde edilen bu teorik veri EPA'nın (Environmental Protection Agency) kanser riskine ilişkin hedef risk seviyesinin altında bulunmuştur [71].…”
Section: Asbest Ve Talk Pudrasıunclassified
“…There have been several studies that have attempted to evaluate the potential for exposures to particulates, and more specifically, asbestos, phase-contrast microscopy (PCM)countable fibers, and EMPs associated with the use of cosmetic talcum powders (E. L. Anderson et al, 2017;Aylott et al, 1979;Moon et al, 2011;Rasmussen et al, 2019;Russell et al, 1979;Steffen Tran et al, 2019). Those studies assessing exposures to asbestos specifically have shown inconsistent findings, most likely due to differences in nomenclature and analytical approaches (E. L. Anderson et al, 2017;Burns et al, 2019;Egilman et al, 2019;Gordon et al, 2014) For example, Gordon et al (2014) did not differentiate asbestos from non-asbestos amphibole EMPs because the authors stated that "it is unclear how to identify a cleavage fragment once the stone or material has been finely ground," whereas E. L. Anderson et al (2017) attempted to differentiate asbestos and non-asbestos amphibole EMPs in their analysis of air samples, although the authors also projected risk estimates assuming all EMPs were asbestos.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a monitoring system should be launched to reduce violence and deaths. The preventive approach to health education measurement should be increased and focused heavily on surveillance (Siribunnam et al, 2014;Burns et al, 2019;Taher et al, 2019).…”
Section: Introductionmentioning
confidence: 99%